2011
DOI: 10.1002/bjs.7756
|View full text |Cite
|
Sign up to set email alerts
|

Translational barriers and opportunities for emergency preservation and resuscitation in severe injuries

Abstract: Background: Hypothermia is commonly used for organ and tissue preservation in multiple clinical settings, but its role in the management of injured patients remains controversial. There is no doubt that temperature modulation is a powerful tool, and hypothermia has been shown to protect cells during ischaemia and reperfusion, decrease organ damage and improve survival. Yet hypothermia is a double-edged sword: unless carefully managed, its induction can be associated with a number of complications.Methods: A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…(8) A recent case series has shown that induced hypothermia protocols may be used after traumatic cardiac arrest with positive outcomes. (9) Several laboratory studies have sought to clarify the role of hypothermia during resuscitation from hemorrhagic shock and trauma.…”
Section: Introductionmentioning
confidence: 99%
“…(8) A recent case series has shown that induced hypothermia protocols may be used after traumatic cardiac arrest with positive outcomes. (9) Several laboratory studies have sought to clarify the role of hypothermia during resuscitation from hemorrhagic shock and trauma.…”
Section: Introductionmentioning
confidence: 99%
“…These include the need to decrease the core body temperature to <15°C, requirement for cardiopulmonary bypass, the very short window of time available for complex instrumentation, the need for effective heat-exchange technology or large volume of cold fluids, and the adverse effect of hypothermia on coagulopathy. 10 These limitations are especially problematic in the austere prehospital environment, where most of trauma-related deaths occur.…”
mentioning
confidence: 99%
“…Induction of profound hypothermia (core temperature 10–15°C) requires specialized instrumentation and is therefore technically very challenging (23). Profound hypothermia may also produce adverse side effects that are proportional to the depth of hypothermia, such as inducing coagulopathy and impairing the immune response.…”
Section: Discussionmentioning
confidence: 99%